2017
DOI: 10.1007/s12105-017-0837-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Molecular Characteristics of Familial Cherubism with Associated Odontogenic Tumorous Proliferations

Abstract: Cherubism is a rare autosomal dominant condition affecting the jaws and caused by mutations in the gene encoding for the adapter protein SH3BP2 that maps to chromosome 4p16.3. Cherubism is characterized by symmetrically developing bone lesions in the maxilla and mandible. The lesions have been radiographically and histopathologically well-described. Here, we present a family with cherubism with two of its members featuring odontogenic tumorous proliferations in association with persistent central giant cell le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
8
0
3
Order By: Relevance
“…4 Initial cases may present with lymph node enlargement thus contributing to the cherubic appearance. 2,6 Infiltration of the orbital bone may lead to exophthalmos causing limitation of ocular movements and the typical "eyes raised to heaven" appearance. In the present case, bone involvement was restricted to the posterior mandible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Initial cases may present with lymph node enlargement thus contributing to the cherubic appearance. 2,6 Infiltration of the orbital bone may lead to exophthalmos causing limitation of ocular movements and the typical "eyes raised to heaven" appearance. In the present case, bone involvement was restricted to the posterior mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Cherubism has been associated with a central odontogenic fibroma-like proliferation. Argyris et al 6 reported the development of intraosseous squamous cell carcinoma in a long-standing case of cherubism. Osteosarcoma has been reported in cherubism cases treated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, odontogenic epithelial components were not identified by morphology or by pancytokeratin immunostain (data not shown). 13,14…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, odontogenic epithelial components were not identified by morphology or by pancytokeratin immunostain (data not shown). 13,14 Submandibular and cervical lymph nodes are frequently enlarged during early stages of cherubism. 3 Meng et al 5 reported that the lymphadenopathy was observed in 10 out of 24 patients with cherubism.…”
Section: Molecules and Cytokines Associated With Tooth Eruption Also mentioning
confidence: 99%
“…En este último escenario, la simetría facial del niño se observa distorsionada y la expansión ósea produce una cara redonda similar a un querubín, con mejillas prominentes, y una maloclusión con desplazamiento de las piezas dentales y dificultades de la masticación (1,2,4,8,9,(17)(18)(19). Otros signos y síntomas incluyen adenopatías cervicales y submandibulares, así como dificultades visuales, auditivas o respiratorias; además de dificultad para el habla y disfagia (1,4,17,(19)(20)(21).…”
Section: Presentación Clínicaunclassified